2008
DOI: 10.1111/j.1468-2338.2008.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining activity and exploring experience—findings from a survey of union learning representatives

Abstract: This article draws on data from one of the largest surveys to date of union learning representatives (ULRs) in order to build a unique picture of ULR experience and activity. It is found that ULRs made a contribution to increased diversity and represented an injection of 'new blood' within workplace union structures. Moreover, ULRs with no previous union involvement were just as likely to be active in promoting learning as their more experienced colleagues. At the same time, we found that a significant minorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…Further, UPOs reported that ULRs differed in sex and age from other workplace union representatives. Similar findings are reported by unionlearn (2008) and Hollinrake et al . (2008).…”
Section: Sulf Learning and Union Revitalizationsupporting
confidence: 92%
“…Further, UPOs reported that ULRs differed in sex and age from other workplace union representatives. Similar findings are reported by unionlearn (2008) and Hollinrake et al . (2008).…”
Section: Sulf Learning and Union Revitalizationsupporting
confidence: 92%
“…The results also point to the importance of management support in enabling ULRs to perform the role effectively (as also identified by Hollinrake et al, 2008;Thompson et al, 2007;unionlearn, 2006;Wood and Moore, 2005;Wray, 2007). In total, 37 percent of ULRs state that managers do not value them (a figure not dissimilar from Wallis et al, 2005, who found 45 percent of managers to be indifferent to the ULR role).…”
Section: Discussionmentioning
confidence: 54%
“…The analysis identified a number of factors as important. Starting with ULR activity, as also argued by Hollinrake et al (2008) and Wood and Moore (2005), the number of hours ULRs spend performing the role appears particularly important, with ULRs spending more than five hours per week on ULR activity being more likely to have positively influenced training than those spending less time on the role. This suggests an important role for employers in ensuring that ULRs receive sufficient paid time off to conduct ULR activities.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A further factor that might influence Disability Champion effectiveness concerns the support they receive from their union, from employers and from the broader bargaining environment. Where union support is concerned, support for new types of representatives such as Disability Champions might involve negotiating formal agreements for time off and facilities (Hollinrake et al ., ). However, given the somewhat patchy history of unions in relation to disability (Humphrey, ), it is debatable whether such support will be offered.…”
Section: Factors Associated With Disability Champion Effectiveness – mentioning
confidence: 97%